PENENTUAN KELAYAKAN PENERIMAAN BANTUAN RASKIN DENGAN METODE MOORA PADA KELURAHAN MARTOBA PEMATANGSIANTAR - Siregar, Abdul Zikri; Poningsih, Poningsih; Safii, M (STMIK Budi Darma, 2018)
Raskin is a rice program for the poor. The Raskin program is one of the governments efforts to reduce the burden of expenditure on poor families. However, in its field practice, the decision to determine the criteria for receiving rice that has already taken place usually does not refer to the criteria of poor families, resulting in the distribution of rice being misdirected. To help these problems, a decision support system will be established to assist in the distribution of Raskin which is right on target with the Multi-Objective Optimization Method On The Base Of Ratio Analysis (Moora). Decision Support System (SPK) is a computer-based system combining models and data in an attempt to solve unstructured problems with user involvement through a user interface that is easy to use. This system is used for assist decision making in semitructured situations and unstructured situations, where no one knows exactly how decisions should be made. The Moora method is a multicriteria decision making method based on each appropriate criterion. The criteria used are: Job Type, Amount of Income, Amount of Dependent, House Condition, Home Ownership, Age.Keywords: Decision Support System, Moora, Raskin (Poor Rice)